Solar-Blind Optical Wireless Communications Over 80 Meters Using a 265-nm High-Power Single-Chip DUV-LED Over 500 mW in Sunlight - Hiroyuki Kurosawa; Sachiko Tsuzuki; Manabu Taniguchi; Shin-ichiro Inoue (IEEE Photonics Journal, 2023)
Direct eye-pattern measurements based on a deep-ultraviolet (DUV) light emitting diode (LED) optical wireless communication system were performed in sunlight. A state-of-the-art, high-power DUV-LED was developed and used as a transmitter consisting of only one LED chip with a light output power greater than 500 mW at its peak emission wavelength of 265 nm. A DUV light receiver was also developed that excluded sunlight with high performance. We demonstrated clear eye-patterns at 1 Mbps in both line-of-sight (LOS) and non-line-of-sight (NLOS) configurations over a communication distance of 80 meters in sunlight.